Armenia Towards a "New Economy": Defense Industry - A. B. Harutyunyan (Цифровая трансформация)
In fact, a new arms race could start in the world as a side effect of the so-called “4th Industrial Revolution” – the main innovative trend of which is the widespread use of technologies such as artificial intelligence, machine learning, quantum computing, additive manufacturing, robotics, Internet of things, cloud technologies etc., and the countries involved in military conflicts cannot neglect this circumstance. As a small country, Armenia needs an economy-army coalesced “intelligent” system that will respond adequately to any, even the slightest threat to the country's security. This approach requires the development of indigenous defense industry. It is obvious that the development of Armenian defense industry is in the inevitable point of intersection of the new wave of economic transformations and the breakthrough of the “4th Industrial Revolution”, as the initiator of positive changes in the economy, from which positive externalities must be spread throughout the economy by a chain reaction. The article discusses the issues of defense industry development in Armenia in accordance with new challenges of Industry 4.0.